Microfinancing from the Zakat Fund in Baitul Mal Aceh and the Readiness of Malaysia's Asnaf Entreprenuers - Zahri, Mohd. ‘Adli; Muhd Adnan, Nurul Ilyana; Irfan, Irfan; Mohd Kashim, Mohd Izhar Ariff (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The recent Covid-19 pandemic has swept the globe. As a result, there has been a spike in the number of relative poor who are experiencing economic hardships. This poses a predicament for the unbankable, reducing their options to apply for funding via banking products. With the available financial capacity, zakat institutions are viewed as the closest alternative in terms of being a source of funding, either through the microfinacing method or the qard hasan principle. Zakat is considered capable of becoming a social entrepreneurial system and a worthy alternative. The question is whether Islam permits microfinancing using zakat funds. If permitted, what is the rationale for distributing zakat through microfinance? Are there asnaf entreprenuers in Malaysia ready to take microfinance from the zakat fund to finance their businesses? This study is done using the case study method by conducting a semi-structured interview with zakat expertise and asnaf entreprenuers. Based on the content analysis, the findings of the study indicate that Islam permits microfinance using zakat funds. Asnaf entreprenuers are likewise eager to acquire microfinance from zakat money in order to to strengthen their economic position and develop in life. This microfinancing is expected to have a good effect, particularly on the rising demand for asnaf entreprenuers. So, it is expected that asnaf entreprenuers will be able to switch from being a zakat recipient to a zakat payer within a certain amount of time.